Deciphering the molecular mechanisms behind cellulase production in Trichoderma reesei, the hyper-cellulolytic filamentous fungus. Issue 9 (1st September 2016) - Shida, Yosuke; Furukawa, Takanori; Ogasawara, Wataru
Abstract: The filamentous fungus Trichoderma reesei is a potent cellulase producer and the best-studied cellulolytic fungus. A lot of investigations not only on glycoside hydrolases produced by T. reesei, but also on the machinery controlling gene expression of these enzyme have made this fungus a model organism for cellulolytic fungi. We have investigated the T. reesei strain including mutants developed in Japan in detail to understand the molecular mechanisms that control the cellulase gene expression, the biochemical and morphological aspects that could favor this phenotype, and have attempted to generate novel strains that may be appropriate for industrial use. Subsequently, we developed recombinant strains by combination of these insights and the heterologous-efficient saccharifing enzymes. Resulting enzyme preparations were highly effective for saccharification of various biomass. In this review, we present some of the salient findings from the recent biochemical, morphological, and molecular analyses of this remarkable cellulase hyper-producing fungus. Graphical abstract: : For Trichoderma reesei, transcriptional regulation of cellulolytic enzyme genes, comparative genomics and morphological insights, and applications of them were summarized.